2018
DOI: 10.1115/1.4039976
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study on a Subcritical CO2/NH3 Cascade Refrigeration System for Low Temperature Applications

Abstract: Adverse effects of synthetic refrigerants on the environment have led to replacing them with natural refrigerants. The common candidates are ammonia, carbon dioxide, and several hydrocarbon compounds and their mixtures. Ammonia has been used mainly in large-scale cooling purposes such as large-scale supermarkets and climatic rooms. However, in such systems, leakage of ammonia may arise severe results on human health and may damage products in the cooled space. Recently, in last decade, a well-known refrigerant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…To evaluate the environmental consequences of mixed refrigerant leakage, the annual leak rate is calculated for the fifteen case studies listed in Table 3. Equation (17) shows the annual leak rate equivalent to tonne-CO 2 ; LR MR,Annual = . m MR * t * LR * GWPI MR * 3600/1000 (17) where the mixed refrigerant mass flow rate of a mixed refrigerant is multiplied by number of operation hours in a year (t), leak rate (LR) which is considered to be 0.5%, and GWPI [46,47].…”
Section: Environmental Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate the environmental consequences of mixed refrigerant leakage, the annual leak rate is calculated for the fifteen case studies listed in Table 3. Equation (17) shows the annual leak rate equivalent to tonne-CO 2 ; LR MR,Annual = . m MR * t * LR * GWPI MR * 3600/1000 (17) where the mixed refrigerant mass flow rate of a mixed refrigerant is multiplied by number of operation hours in a year (t), leak rate (LR) which is considered to be 0.5%, and GWPI [46,47].…”
Section: Environmental Analysismentioning
confidence: 99%
“…Equation (17) shows the annual leak rate equivalent to tonne-CO 2 ; LR MR,Annual = . m MR * t * LR * GWPI MR * 3600/1000 (17) where the mixed refrigerant mass flow rate of a mixed refrigerant is multiplied by number of operation hours in a year (t), leak rate (LR) which is considered to be 0.5%, and GWPI [46,47]. Due to continuous refrigerant leakage, LNG plants need to purchase the makeup refrigerants.…”
Section: Environmental Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…They indicated that the employment of the ejectors has considerable effect on the performance of the conventional cascade system. Yilmaz et al [15] examined mathematically the performance of a two-stage subcritical CO 2 /NH 3 cascade refrigeration system for different operating conditions. They proposed correlations to predict the maximum COP for given operation parameters.…”
Section: Introductionmentioning
confidence: 99%